A Highly Emissive Surface Layer in Mixed‐Halide Multication Perovskites. Issue 42 (6th September 2019) - Andaji‐Garmaroudi, Zahra; Abdi‐Jalebi, Mojtaba; Guo, Dengyang; Macpherson, Stuart; Sadhanala, Aditya; Tennyson, Elizabeth M.; Ruggeri, Edoardo; Anaya, Miguel; Galkowski, Krzysztof; Shivanna, Ravichandran; Lohmann, Kilian; Frohna, Kyle; et al.
Abstract: Mixed‐halide lead perovskites have attracted significant attention in the field of photovoltaics and other optoelectronic applications due to their promising bandgap tunability and device performance. Here, the changes in photoluminescence and photoconductance of solution‐processed triple‐cation mixed‐halide (Cs0.06 MA0.15 FA0.79 )Pb(Br0.4 I0.6 )3 perovskite films (MA: methylammonium, FA: formamidinium) are studied under solar‐equivalent illumination. It is found that the illumination leads to localized surface sites of iodide‐rich perovskite intermixed with passivating PbI2 material. Time‐ and spectrally resolved photoluminescence measurements reveal that photoexcited charges efficiently transfer to the passivated iodide‐rich perovskite surface layer, leading to high local carrier densities on these sites. The carriers on this surface layer therefore recombine with a high radiative efficiency, with the photoluminescence quantum efficiency of the film under solar excitation densities increasing from 3% to over 45%. At higher excitation densities, nonradiative Auger recombination starts to dominate due to the extremely high concentration of charges on the surface layer. This work reveals new insight into phase segregation of mixed‐halide mixed‐cation perovskites, as well as routes to highly luminescent films by controlling charge density and transfer in novel device structures. Abstract : The changes in photophysical properties of mixed‐halide perovskite films under solar‐equivalent illumination are studied. The illumination generates localized low‐bandgap surface domains, onto which photoexcited charge carriers transfer and recombine with high radiative efficiency. The fraction of radiative and nonradiative (Auger) recombination bandgap can be balanced to achieve extremely high photoluminescence quantum yields at low excitation densities.